A fuzzy basis real-time monitoring system designed for the control of cutting tools in flexible manufacturing cells. (1st January 2001) - Ip, Ralph W.L.; Lau, Henry; Chan, Felix T.S.
In a flexible machining cell (FMC), cutting tools are always considered as an essential component. Therefore, tool control is a vital managerial decision function in an FMC among groups of computer-controlled machines. A Tool Monitoring System (TMS) as proposed in this paper is a piece of large-scale computing software and it consists of an offline part and tool assignment model and a real-time tool information monitoring mechanism. In the parts and tools scheduling process, the part geometrical features, work flow information and tool availability factors are considered to determine a part priority weight. Parts with a high weighting will always be assigned to the machining schedule earlier than the tools with a low weighting. The part priority weight is calculated by using fuzzy approaches based on the information from tools and part relationships. An industrial case study is given in this study to demonstrate the capability of the TMS and how the real-time monitoring mechanism works for a machine breakdown case.